Penurunan Persediaan Spare Part di PT. XYZ - Anthony Gunadi; I Gede Agus Widyadana (Jurnal Titra, 2015)
The value of spare part inventory in company is high because there are so many non moving spare part. The purpose of this research is to reduce spare part inventory by ditributing questionnaires about spare parts status And analyzing the amount of inventory and creating a form of PR and purchase history. Status of spare part is divided into three kinds, they are status A, status B, and status C. Status A is intended for spare parts that are still in use, status B is intended for spare parts that are not used anymore, and status C is intended for spare parts that have been damaged. Status A is analyzed from the economic side of inventory amount to decide whether it should be kept or written off. Form PR and purchase history is made to help facilitate the recording of purchases of spare parts. The results shows through write off can reduce inventory amount up to 4,57% dan the value of inventory decreased up to Rp 216,432,253.00. The result also shows the analyze of inventory amount can save the cost up to Rp. 8,592,063.00 for Electrical Maintenance Department’s spare part.